1992
DOI: 10.1111/j.1365-2842.1992.tb01583.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of two methods for the orientation of the occlusal plane and the determination of the vertical dimension of occlusion in edentulous patients

Abstract: The aim of this study was to compare two methods used to orientate the occlusal plane (OP) and to determine the vertical dimension of occlusion (VDO). In method A the VDO was established by means of the rest position, the minimal speaking distance, and the patient's profile. Method B used a newly developed registration pin assembly. The VDO was registered using a silicone occlusion rim and the swallowing technique. The results were compared to the values of the new dentures. Three standardized lateral radiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 42 publications
1
22
0
2
Order By: Relevance
“…The anterorotation of the occlusal plane in our group is in agreement with observations made by Gsellmann et al . (1995) and Koller et al . (1992).…”
Section: Discussionmentioning
confidence: 97%
“…The anterorotation of the occlusal plane in our group is in agreement with observations made by Gsellmann et al . (1995) and Koller et al . (1992).…”
Section: Discussionmentioning
confidence: 97%
“…and Karkazis and Polyzois reported it as 7.00° and 10.00° respectively. [61836] Seifert et al . has concluded occlusal plane-FH plane angulations as 11.42° in dentulous subjects whereas Celebic et al .…”
Section: Discussion and Conclusive Remarksmentioning
confidence: 99%
“…It is therefore not possible for the EMG to be used as a measure. It has been suggested that the act of swallowing could be useful for the evaluation of vertical dimension, because at this point the mandible is said to be placed in the "correct" vertical dimension Laird, 1976Laird, , 1989Koller et al, 1992). Even for some of its advocates, this method has not been sufficiently evaluated (Mohindra, 1996), and, in any case, it is no more objective than the other techniques.…”
Section: (112) Effects Of a Modification Of Head Position On The Antmentioning
confidence: 99%